Maturing neutrophils of lower density associate with thrombocytopenia in Puumala orthohantavirus-caused hemorrhagic fever with renal syndrome - Cabrera, Luz E.; Tietäväinen, Johanna; Jokiranta, Suvi T.; Mäkelä, Satu; Vaheri, Antti; Mustonen, Jukka; Vapalahti, Olli; Kanerva, Mari; Strandin, Tomas (Frontiers in Immunology, 2024)
Puumala orthohantavirus-caused hemorrhagic fever with renal syndrome (PUUV-HFRS) is characterized by strong neutrophil activation. Neutrophils are the most abundant immune cell type in the circulation and are specially equipped to rapidly respond to infections. They are more heterogenous than previously appreciated, with specific neutrophil subsets recently implicated in inflammation and immunosuppression. Furthermore, neutrophils can be divided based on their density to either low-density granulocytes (LDGs) or "normal density" polymorphonuclear cell (PMN) fractions. In the current study we aimed to identify and characterize the different neutrophil subsets in the circulation of PUUV-HFRS patients. PMNs exhibited an activation of antiviral pathways, while circulating LDGs were increased in frequency following acute PUUV-HFRS. Furthermore, cell surface marker expression analysis revealed that PUUV-associated LDGs are primarily immature and most likely reflect an increased neutrophil production from the bone marrow. Interestingly, both the frequency of LDGs and the presence of a "left shift" in blood associated with the extent of thrombocytopenia, one of the hallmarks of severe HFRS, suggesting that maturing neutrophils could play a role in disease pathogenesis. These results imply that elevated circulating LDGs might be a general finding in acute viral infections. However, in contrast to the COVID-19 associated LDGs described previously, the secretome of PUUV LDGs did not show significant immunosuppressive ability, which suggests inherent biological differences in the LDG responses that can be dependent on the causative virus or differing infection kinetics. Max Systolic BP (mmHg) 99 -185 (134.1 + 20.2) < 120 Max Diastolic BP (mmHg) 64 -102 (82.7 + 10.4) < 80 Min Systolic BP (mmHg) 70 -143 (104.7 + 18.6) < 120